KINERJA PELAYANAN PUBLIK DI KANTOR KECAMATAN TAWAELI KOTA PALU - Zainudin, Zainudin (Katalogis, 2015)
This research aims at finding out the public service performance at Tawaeli subditrict office Palu. This is a descriptive research, giving overview, description, and detail interpretation of data about the public service performance. This research used field research, in which the information was collected directly from the informant.This research applied the performance theory proposed by Kumorotomo, employing several indicators, they are efficiency, effectiviness, fairness, and responsiviness. The data were collected trough there stages : data reductions, data display, and conclusion. The tecniques of data collection were observation, interview, and documentation.The six informants wre taken trough purposive. The results show that the public service performance in Tawaeli subdistrict office Palu was still low and there are several things thad need to be addressed to make the public serviceperformance better. Based on the four indicators, effectiviness is the only aspect that still needs to be improved. It is caused by the lack of facilities and infrastructure at Tawaeli subdristrict office Palu.